Physical fitness in young male athletes in relation to chronological age and sexual maturation - Böhme, M. T. S.; Kiss, M. A. P.; Regazzini, M.; Rodrigues, R. L.; Massa, M.; Uezu, R. (2001)
The aim of this study was to describe the development of physical fitness components of young male athletes, with respect to a)the different sexual maturation stages and b) the different chronological ages, as well as to verify the existence of significant differences among the different sexual stages in each age group. A total of 218 young male athletes from track and fields (N=110) and soccer (N=108) were divided in two age groups: group 1 (N=96), from 12 to 13 years old; group 2 (N=122), from 14 to 16 years old. Seven performance tests included the horizontal jump, 3 kg medicine ball throw, sit-ups in 30s, 9 minutes run, sit and reach, agility and 30m dash. Sexual maturity stages were defined using pubic hair and genitalia development (Tanner, 1962). For each performance variable one way ANOVA was used among the sexual stages for pubic hair and genitalia development in each age group. The results regarding the significant effects of the sexual maturation (p<0.05) are presented in the Table. The sexual maturation had significant effect on the arms and legs strength in both age groups, as well on the velocity in the older group. Otherwise, the sexual maturation had no significant influence (p<0.05) on the other performance variables in both age groups.